Devaluation processes in the conditions of world crisis. (Journal of Economic Research & Business Administration, 2016)
Devaluation processes in the conditions of world crisis is an inevitable attribute of a market economy. For Kazakhstan, like other countries, under the circumstances, the measure was inevitable. First of all, it allows you to increase the competitiveness of the economy, to improve the working conditions of exporters, which will save or create jobs, as well as less costly to get out of the crisis. As a result of the devaluation is less spent foreign exchange reserves of the country, created the necessary conditions inflow of foreign capital. Devaluation processes proved to measures aimed at improving the economic parameters of the country in the first place – for domestic enterprises. Due to the reduction in price of KZT economic actors receive an additional profit, which generally have a positive impact on the economy of the republic.
Keywords: devaluation processes; economy; crisis; foreign exchange reserves.